Numbered Head Together To Foster Reading Comprehension And Self-Confidence In For Pesantren Students - Muda'i, Muda'i; Budhi Ningrum, Ary Setya; Ummah M, S. Sumihatul (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2024)
Abstract This study focuses on seeing the effectiveness of the application of Numbered Head Together (NHT) in helping to learn cooperatively and developing students' confidence in their reading comprehension in the English area environment at the secondary level in the Karang Durin Islamic boarding school, the findings of this study showed that the use of the Numbered Head Together (NHT) method was able to encourage and maximize student collaboration, Active participants, able to build students' self-confidence and increase cooperation possessed by students in groups, to build reading learning comprehension more enjoyable. Researchers acknowledge the lack of limitations due to limited sample size and duration, but this study still underlines further research to provide an understanding of the importance of applying cooperative learning methods, Numbered Head Together NHT. This research method used a qualitative approach and proposed a recommendation emphasizing the importance of testing NHT cooperative learning methods in education, as evidenced in proven references.